O trabalho nas cozinhas de unidades escolares: impactos sobre a saúde das merendeiras em escola municipal de São Carlos - Coimbra, Fabiano Bueno (Universidade Federal de São Carlos, 2013)
This work aims to understand the activity of people who work in food preparation at school from an understanding of the factors that influence and determine that work. The need arose from the demand of the city of São Carlos, which identified several problems faced by employees who perform the function of cook staff, problems that resulted in several complaints and absenteeism due to health problems in developing the activities and productivity. As a working methodology a case study was used through a set of data collected from a municipal school unit of São Carlos, and using methodological fundamentals of Ergonomic Work Analysis, the presented work situation was analyzed based on the fundamentals of ergonomics and situated criteria workplaces. The results are expected to generate a set of inferences and knowledge in order to serve as a basis for designing and dimensioning units of food and nutrition in public schools.
Keywords: Ergonomia; Análise ergonômica do trabalho; Cozinhas; Merendeiras; Situação de trabalho; Work situation; Kitchen; Cook staff; ENGENHARIAS::ENGENHARIA DE PRODUCAO